The CBP-1/p300 Lysine Acetyltransferase Regulates the Heat Shock Response in C. elegans - Barrett, Lindsey N.; Westerheide, Sandy D. (Frontiers in Aging, 2022)
The decline of proteostasis is a hallmark of aging that is, in part, affected by the dysregulation of the heat shock response (HSR), a highly conserved cellular response to proteotoxic stress in the cell. The heat shock transcription factor HSF-1 is well-studied as a key regulator of proteostasis, but mechanisms that could be used to modulate HSF-1 function to enhance proteostasis during aging are largely unknown. In this study, we examined lysine acetyltransferase regulation of the HSR and HSF-1 in C. elegans. We performed an RNA interference screen of lysine acetyltransferases and examined mRNA expression of the heat-shock inducible gene hsp-16.2, a widely used marker for HSR activation. From this screen, we identified one acetyltransferase, CBP-1, the C. elegans homolog of mammalian CREB-binding protein CBP/p300, as a negative regulator of the HSR. We found that while knockdown of CBP-1 decreases the overall lifespan of the worm, it also enhances heat shock protein production upon heat shock and increases thermotolerance of the worm in an HSF-1 dependent manner. Similarly, we examined a hallmark of HSF-1 activation, the formation of nuclear stress bodies (nSBs). In analyzing the recovery rate of nSBs, we found that knockdown of CBP-1 enhanced the recovery and resolution of nSBs after stress. Collectively, our studies demonstrate a role of CBP-1 as a negative regulator of HSF-1 activity and its physiological effects at the organismal level upon stress.